Analisis Pengaruh Variabel Makro Ekonomi Terhadap Prevalensi Stunting Di Indonesia - Viezani, Ezra Shafa; Yeni, Isra; Rahmizal, Maizul (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2024)
This study aims to analyze the influence of Poverty, Economic Growth Rate, Government Policy and Exclusive Breastfeeding on Stunting Prevalence in Indonesia. This study uses a panel data regression analysis method with a Random Effect Model (REM). The results of the study show that Poverty has a significant positive effect on Stunting Prevalence, and Government Policy and Exclusive Breastfeeding have a significant negative effect on Stunting Prevalence, and Economic Growth Rate has no effect on Stunting Prevalence in Indonesia.